ANALISIS PERPUTARAN KAS, PERPUTARAN PERSEDIAAN DAN LIKUIDITAS TERHADAP PROFITABILITAS DI BURSA EFEK INDONESIA - Erlina, Erlina; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2021)
Development of a company depends on its profitability. It can be said that the most important thing from the financial statements for investors and potential investors. the fluctuation in profit is very influential on the company. The number of population studied in this study consisted of 29 food and beverage sub-sector companies on the Indonesia Stock Exchange 2015-2019. The results obtained were 9 samples that had passed the listed criteria. The sampling method used in this study was purposive sampling and the data used in this study were secondary data. The influence test in this study used multiple linear regression analysis using the SPSS version 25 software program. Based on the result of the t test, it can be concluded that cash turnover partially has no effect and has no significant effect on profitability, inventory turnover is partially influential and has significant effect on profitability, liquidity partially has no effect and has no significant effect on profitability. While the result of the f test stated that cash turnover, inventory turnover and liquidity simultaneously have an effect and are significant on profitability.